Victims of Terrorism. The Question of the Narrative - Castells Arteche, Luis (Huarte de San Juan. Geografía e Historia, 2014)
The text reviews the treatment being received by the victims of terrorism in the Basque Country and the different options that are being put into play. Emphasis is placed on the risk of equating different types of violence, or of making a benevolent and accommodating reading of the past. Underlying the article is the idea that any narrative construction of the past must be placed in historical context, which underscores the necessary role of the historian when it comes to explaining recent events.